Parameter Identification and PID tuning of DC Motor Speed Control System - Anton
The DC Motor Speed Control Experiment has been taught on Mechanical Engineering program study at Institut Teknologi Bandung since 2014. Even though the program has been taught for five years, the mathematical model of the DC motor speed control system is still not well identified. Research to find the model of the system as first order system with delay time had been carried out. However, the simulation and the experiment from this FODT model are still not proper. The research aim is to identify and validate the model of DC motor control speed system, also to compare some methods of PID tuning. To achieve the aim of this research, static gain and dynamic model of each device that builds up the DC motor control speed system need to identify. Static gain value obtained by measuring response on steady-state condition. While the dynamic model obtained by step response experiment on the open-loop system. From each model obtained by experiment, the whole dynamic model of DC motor control speed system can be build up and validating. After the model had been validated, the system is modeled as FODT. So that the PID tuning of Ziegler-Nichols, Cohen-Coon, and Chien-Hrones-Reswick methods can be applied. To compare the result of PID tuning methods, error value from step response on closed-loop control is calculate with Integral Absolute Error method. From the experiment, the dynamic model of DC motor speed control system had been well identified and validated. Besides that, the method that had the minimum error for P and PID controller is Cohen-Coon tuning method, and for PI controller is CHR tuning method.